2022
DOI: 10.1371/journal.pone.0278707
|View full text |Cite
|
Sign up to set email alerts
|

Longitudinal analyses and predictive factors of radiation-induced lung toxicity-related parameters after stereotactic radiotherapy for lung cancer

Abstract: Background and purpose The purpose of this prospective study was to investigate changes in longitudinal parameters after stereotactic radiotherapy for lung cancer and to identify possible pretreatment factors related to radiation-induced lung toxicity and the decline in pulmonary function after radiotherapy. Materials and methods Protocol-specified examinations, including 4-D CT, laboratory tests, pulmonary function tests (PFTs) and body composition measurements, were performed before SRT and at 1 month, 4 m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 41 publications
0
2
0
Order By: Relevance
“…Currently, surgery, chemotherapy, radiation, and targeted molecular treatment are the main treatment options for LC patients ( South et al, 2020 ). However, the side effects and toxicity of these techniques have become limiting factors in the clinical treatment of lung cancer ( Luan et al, 2015 ; Yamamoto et al, 2022 ).…”
Section: The Protection Of Ba Against Respiratory Diseasesmentioning
confidence: 99%
See 1 more Smart Citation
“…Currently, surgery, chemotherapy, radiation, and targeted molecular treatment are the main treatment options for LC patients ( South et al, 2020 ). However, the side effects and toxicity of these techniques have become limiting factors in the clinical treatment of lung cancer ( Luan et al, 2015 ; Yamamoto et al, 2022 ).…”
Section: The Protection Of Ba Against Respiratory Diseasesmentioning
confidence: 99%
“…Currently, surgery, chemotherapy, radiation, and targeted molecular treatment are the main treatment options for LC patients (South et al, 2020). However, the side effects and toxicity of these techniques have become limiting factors in the clinical treatment of lung cancer (Luan et al, 2015;Yamamoto et al, 2022). Sui et al (2020) found that 20 mg/kg of BA can trigger apoptosis and block cell cycle G1/S transition in carcinoma of the lung cells via the AKT/mechanistic target of rapamycin (mTOR) pathway.…”
Section: Lung Cancermentioning
confidence: 99%